The time dependent influence of curvature and topography of biomaterials in the behavior of corneal endothelial cells - Bosch, Begoña M.; Delgado, Luis M.; Rodríguez-González, Raquel; Perez, Roman A. (Frontiers in Bioengineering and Biotechnology, 2024)
Among the different layers of the cornea, the corneal endothelium, which is composed of corneal endothelial cells (CEC), plays a key role in the maintenance of cornea transparency. Based on the donor shortages and the limitations associated with transplantation, in this work we have developed collagen hydrogels with different patterned structures on the surface to provide topographies in ranges similar to the natural environment that CEC sense. This aimed at stimulating cells to maintain a typical CEC phenotype and provide alternatives to corneal transplantation. In this sense, we have elaborated curved collagen hydrogels (concave and convex) with three different topographies (50, 200 and 300 µm grooves), with the help of 3D printed mold and replicating the mold with the collagen hydrogel, onto which CEC were cultured in order to analyze its behavior. Flat hydrogels were used as controls. Cell morphology, cell circularity and gene expression of ATP1A1 and ZO-1 genes were analyzed after 3 and 6 days. Results showed an effect of the curvature and the topography compared to flat collagen hydrogels, showing higher expression of ZO-1 and ATP1A1 in curved non-patterned hydrogels at day 3. The patterned hydrogels did not have such a significant effect on gene expression compared to flat hydrogels, showing stronger effect of the curvature compared to the topography. The effect was opposite at day 6, showing higher gene expression at days 6 on the patterned hydrogels, especially for the ZO-1 gene. The gene expression results were in accordance with the cell morphology observed at the different time points, showing circularities closer to hexagon like morphology at shorter time points. Overall, this platform can serve as a system to culture cell under proper environment to further be able to transplant a CEC monolayer or to allow transplantation of thin collagen layers with cultured CEC.